2009
DOI: 10.1007/s10531-009-9681-8
|View full text |Cite
|
Sign up to set email alerts
|

Didymosphenia geminata (Protista, Bacillariophyceae) invasion, resistance of native periphyton communities, and implications for dispersal and management

Abstract: Historically described as cosmopolitan but rare, the benthic diatom Didymosphenia geminata is now considered a nuisance, bloom-forming and invasive species. In New Zealand, D. geminata was first recorded in 2004 in the lower Waiau River. By winter 2008 it had been identified in 26 major catchments. To investigate invasion success of D. geminata in relation to succession and biomass accumulation of native periphyton communities, we conducted a two-factorial field experiment. Seven successional stages of a nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…[37] Current evidence for a dual nutrient-source strategy in D. geminata is limited to our observations of flow-dependent changes in transport processes within mats, low ambient nutrient-concentrations in D. geminata-dominated rivers, and large quantities of POM within and beneath D. geminata mats (Flöder and Kilroy 2009;Whitton et al 2009). More compelling evidence would include high concentrations of dissolved nutrients and/or high rates of POM remineralization in mat matrices, and demonstration of mass transport-limited nutrient uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Current evidence for a dual nutrient-source strategy in D. geminata is limited to our observations of flow-dependent changes in transport processes within mats, low ambient nutrient-concentrations in D. geminata-dominated rivers, and large quantities of POM within and beneath D. geminata mats (Flöder and Kilroy 2009;Whitton et al 2009). More compelling evidence would include high concentrations of dissolved nutrients and/or high rates of POM remineralization in mat matrices, and demonstration of mass transport-limited nutrient uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these harsh conditions, D. geminata mats can reach densities >1000 g ash‐free dry weight m − 2 and dominate the benthos in terms of cover and biomass (Kirkwood et al 2007; Miller et al 2009; Kilroy et al 2009). D. geminata mats overgrow and kill native periphyton, and they are efficient traps for seston (Flöder and Kilroy 2009). As a result, mats are often underlain by and impregnated with nutrient‐rich particulate organic matter (POM) (Whitton et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Currently neither of the upper or lower flow related threshold values are known for quantifying the potential for colonization of the substrate by D. geminata. It has been shown that colonization of D. geminata cells after a disturbance event is indeed influenced by the micro‐topography of the substrate material [ Bergey et al , 2010] and the concentration of new cells arriving from upstream [ Flöder and Kilroy , 2009]. The presence of residual D. geminata mats is therefore also likely to affect the colonization of new cells because of the impact of the mats on the near‐bed hydraulic conditions [ Larned et al , 2011].…”
Section: Colonization and Recovery After Disturbancementioning
confidence: 99%
“…Serra et al (2009) looked at metal accumulation kinetics during biofilms colonization. Two papers about an invasive species (Floder & Kilroy, 2009;Kilroy et al, 2009), Dydimosphaena geminata, studied its colonization process and the evolution of its biomass on various substrates in New Zealand rivers; these studies do not assess the effect of any metal or pesticide, however-they were categorized in this group because of the presence of the same indicative word (colonization) in their abstracts.…”
Section: Ecotoxicology (Group Of Papers #6)mentioning
confidence: 99%